Mediation Model of Service Quality and Behavioural Intention to Use of Artificial Intelligence Security Technology in UAE - Alafreet Alkuwaiti, Salem Ahmed Abdulla; Ahmad, Ahmad Nur Aizat; Abo Mosali, Najmaddin (International Journal of Sustainable Construction Engineering and Technology, 2023)
This study created and evaluated a mediation model which allows the role of essential artificial intelligence (AI) in mediating the connection between service quality and behavioural intent to use AI security features in the United Arab Emirates. The primary objective is to improve the standards for customer service in the UAE's artificial intelligence security industry. The data to developed the model was derived from 389 valid questionnaires form the questionnaire survey. The data was screened and cleaned before uploaded in Smart-PLS software to developing and assessing the model. Based on the assessment on the model, it was found that the most fundamental form of artificial intelligence exerts a mediating effect to some extent, on the connection that exists between service quality and behavioural intention in terms of the application of Al security technology. The coefficient and t-value point to a substantial indirect relationship between the quality of the service and the intention to use artificial intelligence. This relationship is shown to be indirect rather than direct. It is possible to draw the conclusion that improved service quality raises people's likelihood of intending to use AI security technologies. This is due to the fact that the contribution of such technologies to improved job performance, as well as the convenience with which such technologies can be utilised, raises people's awareness of the perceived value of such technologies.